Local Identity, Global Vision: Sustainable Branding Strategies for Coffee Production in Indonesian Agropolitan Region - Abd. Syakur; Imam Santoso; Bunga Hidayati (Yayasan Darussalam Bengkulu, 2026)
Indonesian coffee products face increasingly intense competition in both domestic and international markets, making sustainable branding a strategic requirement for agropolitan regions with strong local identities. This study analyzes the priority factors that influence purchasing decisions for Kapiten Coffee in Pasuruan Regency and formulates a sustainable brand image strategy based on local identity, consumer value, and digital market visibility. The research employed a mixed-method design by combining field observation, consumer-oriented survey indicators, semi-structured stakeholder input, and the Analytical Hierarchy Process (AHP). The criteria examined were product quality, promotion, price, and brand image, while the sub-criteria reflected performance, features, conformity, durability, reliability, service, aesthetics, perceived quality, advertising, social media exposure, discounts, sampling, souvenirs, price affordability, price-quality fairness, price-benefit fairness, competitive price, brand association, consumer experience, perceived product quality, uniqueness, brand personality, and lifestyle congruence. The AHP results show that promotion was the strongest priority criterion (0.2978; 30%), followed by product quality (0.27577; 28%), price (0.2158; 22%), and brand image (0.2107; 21%). At the global indicator level, advertising and promotional visibility achieved the highest weighted score (0.132), followed by product performance (0.088), brand association (0.082), social media exposure (0.073), and price-quality fairness (0.064). These findings indicate that Kapiten Coffee requires an integrated strategy that uses promotion as an entry point for brand awareness while strengthening product consistency, locally rooted storytelling, experiential marketing, and sustainable value communication. The study contributes to agropolitan coffee marketing by demonstrating how AHP-based prioritization can transform fragmented promotional activities into a structured sustainable branding roadmap for local coffee competitiveness.